Analysis of Understanding and Attitudes of the Muntilan District Community towards Cell Phone Waste - Alya Afra Inas Nur; Agra Dewi Sabrina; Cindy Nurshillah; Daravita Anggorowati; Eka Rachma Putri; Hashfi Hawali Abdul Matin (Diponegoro University, 2023)
One of the wastes that includes hazardous and toxic waste is electronic waste. Electronic waste such as phone waste is classified as hazardous and toxic waste based on Government Regulation of the Republic of Indonesia No. 101 of 2014. The number of cellular phone uses in Indonesia is increasing every year, the increasing number of cellular phone users in Indonesia has an impact on the amount of cellular phone waste that if not accompanied by the treatment of cellular phone waste as hazardous and toxic waste will harm the environment. This research aims to determine the understanding of the people of Muntilan District towards electronic waste (cell phone) and to determine the attitude of the people of Muntilan District towards unused cell phones. This research uses descriptive methods with quantitative and qualitative analysis. The data used in the study consists of primary and secondary data, where primary data is obtained through structured interviews. The data obtained from this study are people in Muntilan District are quite familiar with hazardous and toxic waste but most of them did not recognize that cell phone wastes are included in the category of hazardous and toxic waste. The community’s attitudes towards unused cellular phones are to keep the phone.